The Influence of Physical Exercise on Adolescent Personality Traits: The Mediating Role of Peer Relationship and the Moderating Role of Parent–Child Relationship - Liao, Yi; Cheng, Xiaoyu; Chen, Wei; Peng, Xiaowei (Frontiers in Psychology, 2022)
Adolescence is a critical period for the formation of individual personality traits, which are influenced by numerous factors such as the internal and external environment. Physical exercise, an important factor affecting the healthy development of adolescents, whether plays an important role in the formation of adolescents' personality traits and how it works deserves further investigation. Based on the human ecosystem theory, this study explored the relationship between physical exercise and adolescent’ personality traits, as well as the mediating effect of peer relationship and the moderating effect of parent-child relationship on the relationship between physical exercise and adolescent’ personality traits using data from 9284 China Education Panel Survey. The stratified linear regression results showed that physical exercise could significantly positively affect the development of adolescents’ personality traits, but the relationship between physical exercise and adolescent’s personality traits presented a nonlinear inverted U-shaped curve. Peer relationship plays a mediating effect in physical exercise and adolescents' personality traits. The direct effect of physical exercise on adolescent personality traits and that of the peer relationship on adolescent personality traits are moderated by parent-child relationship.